From Leflunomide to Teriflunomide: Drug Development and Immunosuppressive Oral Drugs in the Treatment of Multiple Sclerosis - Lilian Aly; Bernhard Hemmer; Thomas Korn (2017)
Immunosuppressive drugs have been used in the treatment of multiple sclerosis (MS) for a long time. Today, orally available second generation immunosuppressive agents have been approved or are filed for licensing as MS therapeutics. Due to semi-selective targeting of cellular processes, these second-generation immunosuppressive compounds might rather be immunomodulatory. For example, Teriflunomide inhibits the de novo pyrimidine synthesis and thus only targets rapidly proliferating cells, including lymphocytes. It is used as first line disease modifying therapy (DMT) in relapsing-remitting MS (RRMS).